Outcomes after early and delayed rehabilitation for exacerbation of chronic obstructive pulmonary disease: a nationwide retrospective cohort study in Japan - Hiroki Matsui; Taisuke Jo; Kiyohide Fushimi; Hideo Yasunaga (Respiratory Research, 2017)
Abstract Background The effectiveness of early pulmonary rehabilitation (PR) for exacerbation of chronic obstructive pulmonary disease (COPD) remains controversial. The present study aimed to compare the outcomes between early and delayed PR for exacerbation of COPD, using a national inpatient database. Methods Using the Japanese Diagnosis Procedure Combination database, we examined patients who were transported to hospital for exacerbation of COPD, received PR during hospitalisation, and were discharged to their home. The patients were divided into those who received early PR (defined as PR starting within 48 h of admission) and those who received delayed PR. The outcomes included 90-day readmission, length of stay (LOS), and activities of daily living (Barthel index ≥15) at discharge. Multiple imputation was used for missing data. To assess the associations between early PR and the outcomes, we used risk-adjusted treatment effects and instrumental variable methods. Results We identified 12,572 eligible patients, including 8459 patients with delayed PR and 4113 with early PR. In the risk-adjusted treatment effect models, the early PR group had lower proportion of 90-day readmission (risk difference, −3.4%; 95% CI, −5.7% to −1.5%) and shorter LOS (−9.8 days; 95% CI, −10.8 days to −8.7 days) than the delayed PR group. There was no significant difference in activities of daily living at discharge between the two groups. The instrumental variable analyses showed similar results. Conclusions In this national database study, early PR was associated with reduced 90-day readmission and shortened LOS in patients with exacerbation of COPD.